Christian morality in Ghanaian Pentecostalism: a theological analysis of virtue theory as a framework for integrating Christian and Akan moral schemes - Elorm-Donkor, Abraham (Regnum studies in mission, 2017)
Pentecostal "deliverance" theology : a solution to or a problem for morality? -- Pentecostal misunderstanding of Akan worldview -- Virtue ethics : the elements of character as a framework for analysing morality -- Character formation in the Akan moral tradition -- Character formation in John Wesley's moral theology -- Relating Akan and Christian moral schemes